Perspektif Filsafat Cartesian dalam Bimbingan dan Konseling - Idat Muqodas (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
The basic substance of Cartesian philosophy is God, Mind and Material. Descartes philosophical views have contributed to the development of the science of Psychology and Counseling, especially theories that put forward the concept of